KAJIAN PENDEKATAN PEMBELAJARAN STEM DENGAN MODEL PJBL DALAM MENGASAH KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA - Arista Tri Anindayati; Wahyudi Wahyudi (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2020)
Science, Technology, Engineering, and Mathematics (STEM) is an active learning approach to improve (mathematics) students' creative thinking abilities in mathematics learning. In the learning process, STEM combines four main areas, namely knowledge, technology, engineering, and mathematics. Project-Based Learning (PjBL) is a learning model that teaches concepts through a student-centered project so students can work creatively and collaboratively. The purpose of this article is to describe and provide many things related to STEM as an approach that can integrate knowledge, technology, techniques, and mathematics as well as design the implementation of STEM learning approaches with PjBL models to enhance students' creative thinking in mathematics learning. The method used is a literature review. The results of the study show that some essential competencies in mathematics learning can integrate with the STEM approach in the form of routine activity of the STEM approach in the classroom and the provision of projects to students. Thus, the implementation of the STEM approach to mathematics learning can be done in Indonesia to prepare quality human resources and be ready to face challenges and competitions in the industrial revolution era 4.0 in the 21st century.